The use of imagery by soccer players - Salmon, J.; Hall, C.; Haslam, I. (Journal of Applied Sport Psychology, 1994)
Soccer players from national, provincial, and local levels (N = 362) were tested on the Imagery Use Questionnaire. Imagery tended to be used more in conjunction with competition than training and more for motivation (e.g., psyche-ups) than its cognitive function (e.g., practice of skills and strategies). Elite athletes reported more imagery use than non-elite athletes regardless of the function it served. One theoretical model for imagery uses is that of Paivio [Paivio, A. (1985). Cognitive and motivational functions of imagery in human performance. Canadian Journal of Applied Sport sciences, 10, 22S-28S.]. It is presented below in table form to facilitate a better understanding of various imagery uses and forms. Paivio's Model: Functions of Imagery - Specific motivation: Goal-oriented (e.g., winning a game, being best player, selection as All-star) - Specific cognition: Skills (e.g., passing a ball, beating a man, tackling to the line) - General motivation: Affect and arousal (e.g., celebrating the win, the rewards after, parents reacting) - General cognition: Strategies (e.g., setting team in the clear, drawing opposition to your side)